OBSERVATIONS ON THE PRAWN FISHERY OF THE MANDAPAM AREA - Nandakumar, G (Indian Journal of Fisheries, 2011)
Trawling for prawns is carried out at night. The prawn fishery showed annual fluctuations and the average annual prawn catch was estimrjted to be 309.12 tonnes forminig M.lWc of the trEwl landdngs. January to May was the peak season for the fishery contributing 60.6% of the prawn catoh. The average catch per unit for prawns was 27.12 kg. The fishery was chiefly supported by Pemteiis semisulcatus (88.72%) rnd Metapenaeus affinis (11.28%).